All about that base: investigating the role of ligand basicity in pyridyl complexes derived from a copper-Schiff base coordination polymer. Issue 41 (25th July 2019) - Beddoe, Samuel V. F.; Lonergan, Rhona F.; Pitak, Mateusz B.; Price, Jason R.; Coles, Simon J.; Kitchen, Jonathan A.; Keene, Tony D.
Abstract : Ligand p K a and Hammett parameter are key in rationalising the formation of complexes with a soluble copper(ii ) Schiff base unit. Abstract : The role of ligand basicity in complex formation has been investigated using monodentate pyridyls or benzimidazole (mP ) in combination with a solution-stable species derived form a coordination polymer, [Cu(L )] (where L = 2-(2-hydroxybenzylidene-amino)phenol). The 12 [Cu(L )(mP ) n ] complexes generated, combined with the [Cu(L )]2 (pP ) complexes from our previous work (where pP is a polypyridyl ligand), allow us to gauge the likelihood of complex formation based on the p K a of the conjugate acid of the pyridyl ligands and Hammett parameter, σ . Above p K a ≈ 4.5, complexes are formed where the only ligands are L 2− and mP or pP and the packing interactions are predominantly van der Waals. Below this value, complex formation is unlikely unless there are additional oxygen ligands in the Jahn–Teller axis of the Cu(ii ) ion. The structures of two literature [Cu(L )(bP )] complexes, where bP is a chelating bidentate pyridyl ligand are also re-examined to resolve the positional disorder in the [Cu(L )] moiety.